2016
DOI: 10.1093/hmg/ddw158
|View full text |Cite
|
Sign up to set email alerts
|

Tead1 regulates the expression ofPeripheral Myelin Protein 22during Schwann cell development

Abstract: Schwann cells are myelinating glia in the peripheral nervous system that form the myelin sheath. A major cause of peripheral neuropathy is a copy number variant involving the Peripheral Myelin Protein 22 (PMP22) gene, which is located within a 1.4-Mb duplication on chromosome 17 associated with the most common form of Charcot-Marie-Tooth Disease (CMT1A). Rodent models of CMT1A have been used to show that reducing Pmp22 overexpression mitigates several aspects of a CMT1A-related phenotype. Mechanistic studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 93 publications
3
59
0
1
Order By: Relevance
“…Appearance or disappearance of transcription factors will alter its choice of cooperation partners and remove or add either antagonistic or synergistic influences. Stage‐specific changes in the regulatory network composition are likely also responsible for the multiple effects of the Hippo signaling components Yap and Taz on Schwann cell development in combination with Tead transcription factors, in particular Tead1, as their nuclear effectors (Deng et al, ; Grove et al, ; Lopez‐Anido et al, ; Poitelon et al, ).…”
Section: Transcriptional Control Of Peripheral Myelination By Lineagementioning
confidence: 99%
See 1 more Smart Citation
“…Appearance or disappearance of transcription factors will alter its choice of cooperation partners and remove or add either antagonistic or synergistic influences. Stage‐specific changes in the regulatory network composition are likely also responsible for the multiple effects of the Hippo signaling components Yap and Taz on Schwann cell development in combination with Tead transcription factors, in particular Tead1, as their nuclear effectors (Deng et al, ; Grove et al, ; Lopez‐Anido et al, ; Poitelon et al, ).…”
Section: Transcriptional Control Of Peripheral Myelination By Lineagementioning
confidence: 99%
“…Stage-specific changes in the regulatory network composition are likely also responsible for the multiple effects of the Hippo signaling components Yap and Taz on Schwann cell development in combination with Tead transcription factors, in particular Tead1, as their nuclear effectors (Deng et al, 2017;Grove et al, 2017;Lopez-Anido et al, 2016;Poitelon et al, 2016).…”
Section: Transcriptional Control Of Peripheral Myelination By Lineamentioning
confidence: 99%
“…The first reports that studied YAP/TAZ in SCs in vivo confirmed that both mechanotransducers are active in SCs during axon-SC recognition, while SCs are myelinating and after completion of myelination (Poitelon et al, 2016 ; Deng et al, 2017 ; Grove et al, 2017 ). During development, YAP/TAZ regulates SC proliferation, differentiation and myelination programs (Lopez-Anido et al, 2016 ; Poitelon et al, 2016 ; Deng et al, 2017 ; Grove et al, 2017 ). SCs ablated for both YAP/TAZ show an arrest of proliferation, fail to associate with an axon and do not initiate myelination (Poitelon et al, 2016 ; Deng et al, 2017 ; Grove et al, 2017 ).…”
Section: Experimental Approaches To Sc Mechanobiologymentioning
confidence: 99%
“…Consistent with this role, we and others have recently shown that YAP/TAZ promote vigorous proliferation of immature Schwann cells (SC) in developing peripheral nerves (Poitelon et al, 2016; Deng et al, 2017; Grove et al, 2017), and that overexpression of YAP/TAZ promotes tumorigenic proliferation of mature SCs in adult peripheral nerves (Mindos et al, 2017; Wu et al, 2018). Unexpectedly, several groups demonstrated that YAP or YAP/TAZ promote differentiation of developing SCs by upregulating myelin-associated genes, thereby mediating developmental myelination (Fernando et al, 2016; Lopez-Anido et al, 2016; Poitelon et al, 2016; Deng et al, 2017; Grove et al, 2017). Our group additionally showed that YAP/TAZ are selectively expressed in differentiated myelin-forming SCs, and that they are required for maintenance of the myelin sheath in adult nerves (Grove et al, 2017).…”
Section: Introductionmentioning
confidence: 99%